The social capital — the most important part of the capital of business (Путеводитель предпринимателя)
More recently, in Russia it was believed that social capital is a contradiction, paradox, because the «social» is perceived as expensive, but the current state of business notes social capital, which determines the type of device at each stage of economic development of society.